2017
DOI: 10.1016/j.ijscr.2017.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Gastroblastoma, a biphasic neoplasm of stomach: A case report

Abstract: HighlightsGastroblastoma is a rare gastric biphasic tumor with both epithelial and mesenchymal components.To the best of our knowledge only eight cases have been reported in the English literature till date.Surgical excision remains the mainstay of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 8 publications
1
59
0
Order By: Relevance
“…GB is an extremely rare biphasic neoplasm firstly reported by Miettinen et al in 2009 [1]. Since then, only nine reported cases occurred in pediatric age or young adulthood (<30 years) [1, 3–8]. Patients' age ranged from 9–30 years, with a mean of 22.6 years and it was slightly more frequent in men (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GB is an extremely rare biphasic neoplasm firstly reported by Miettinen et al in 2009 [1]. Since then, only nine reported cases occurred in pediatric age or young adulthood (<30 years) [1, 3–8]. Patients' age ranged from 9–30 years, with a mean of 22.6 years and it was slightly more frequent in men (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other authors described similar biphasic gastric tumor in children and young adults and, only recently, Pinto et al [2] observed a case of GB in the adult age. Therefore, to date, only ten case reports describe and illustrate GB among which only one occurred in adulthood [2, 3]. The tumor pathogenesis and biological potential is still unknown, and treatment remains a debatable issue [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, 11 cases have been published so far, solidly supported by morphology, immunophenotype, and, in four instances, by identification of a characteristic MALAT – GLI1 fusion gene . A twelfth ‘gastroblastoma’, questionable because of the presence of cellular atypia significantly deviating from previous canonical examples, has been reported . A gastroblastoma‐like duodenal neoplasm has also been described .…”
Section: Clinicopathological Features Of Published Gastroblastomas Anmentioning
confidence: 91%
“…[1][2][3][4][5][6] A twelfth 'gastroblastoma', questionable because of the presence of cellular atypia significantly deviating from previous canonical examples, has been reported. 7 A gastroblastoma-like duodenal neoplasm has also been described. 8 Finally, a series of six extragastric tumours harbouring GLI1 rearrangements has been published, showing focal cytokeratin positivity and scattered tubular structures in one case (bearing an ACTB-GLI1 fusion), leading to the proposal of an entity defined as 'malignant epithelioid neoplasm with GLI1 fusions'.…”
mentioning
confidence: 99%